Development, Gender and Household Survival in a Kerala Fishery - HOLLY M HAPKE (Economic and Political Weekly March 31, 2001, 2001)
This paper takes a `household survival strategy' approach to understand the impact of economic transformation on artisanal fisherfolk communities. Through a comparative analysis of the survival strategies that fisherfolk households have forged in two communities in Trivandrum district - one Christian, one Muslim - the author examines how development has differentially unfolded in these two locales as a result of different local geographic particularities. This necessarily requires a consideration of women's economic activities as well as an examination of gender ideology and its mediation of men's and women's unique experiences of the development process. Not only do women and men experience economic processes differently as a result of gender, but difference in ideologies of gender help explain, in part, how development can differentially impact separate communities in the same region.